Unveiling the toxic leadership culture in south African universities: authoritarian behaviour, cronyism and self-serving practices - Olabiyi, Olaniyi J.; Du Plessis, Marieta; Van Vuuren, Carel Jansen (Frontiers in Education, 2024)
Introduction: Toxicity among staff members of higher education institutions (HEIs) is often underreported or not reported at all. Experiences of toxic leadership are deemed unmentionable within the consultative and collaborative ideals of HEIs. The underreporting of toxicity among HEI staff may stem from fear of retaliation, inadequate reporting structures, and concerns about alienation or not being taken seriously.The study explored experiences of leadership behaviours in a South African HEI to identify specific dimensions of toxic leadership behaviours. Using an interpretivist qualitative research design, the study involved analysing 39 interviews of secondary data from two datasets gathered by the research team, comprising 25 and 14 participant responses respectively.The study identified four distinct themes of toxic leadership behaviour -authoritarian leadership behaviour, in-group favouritism/groupthink, destructive criticism and self-centrednesswith authoritarianism being the most common behaviour displayed.Presence of toxic leadership within the South African University community, emphasizing the necessity for a comprehensive approach and strategy to address this behaviour.